The sense of coherence and the health behavior of students medical and non-medical universities - Pasieka, Martyna; Zdziarski , Krzysztof (Journal of Education, Health and Sport, 2022)
The article presents the sense of coherence in the perspective of health behaviors of students of medical and non-medical universities. The first part introduces the concepts of the sense of coherence and health-related behaviors. The sense of coherence was explored using the Life Orientation Questionnaire (SOC-29), and health behaviors with the Health Behavior Inventory (IZZ). The group taking part in the study consisted of 216 people - 90 students of medical universities and 126 students of non-medical universities. Research results indicate that there is a relationship between the sense of coherence and health behaviors in the study population. Students of medical and non-medical universities differ statistically significantly in terms of health behaviors. In terms of the sense of coherence, the difference is close to statistical significance, which does not make it possible to present unambiguous conclusions. It was noticed that there is a difference in the declared health behaviors due to gender and that there is a relationship between the frequency of physical activity and health behaviors.